Separation and purification of curcumin using novel aqueous two-phase micellar systems composed of amphiphilic copolymer and cholinium ionic liquids - Kurnik, Isabelle S. (2020)
Novel aqueous two-phase micellar systems (ATPMS) composed of Pluronic F68, a triblock amphiphilic copolymer, and cholinium-based ionic liquids (ILs) were formulated and applied for separation/purification of curcumin (CCM). CCM stability in the presence of ATPMS components was also evaluated. CCM is stable up to 24 h in copolymer (1.0 10.0 wt%) and ILs (0.1 3.0 M) aqueous solutions. Very mild phase separation conditions (close to room temperature) were achieved by adding cholinium ILs to the Pluronic F68 + McIlvaine buffer at pH 6.0 solution. The decrease of cloud-point temperature is dependent on the relative hydrophobicity of IL anion, [Hex] > [But] > [Prop] > [Ac] > Cl. ATPMS composed of more hydrophobic ILs ([Ch][Hex] > [Ch][But] > [Ch][Prop]) are most efficient in the partition of commercial CCM into polymeric micelles-rich phase. The best ATPMS (0.70 M [Ch][But] and 0.60 M [Ch][Hex]-based ATPMS) were then used to purify CCM from a crude extract of Curcuma longa L. Both systems were very selective to separate CCM from protein-based contaminants (selectivity values 25; purification yields 12-fold). Pluronic F68-based ATPMS are promising for selective separation of hydrophobic biomolecules by using cholinium-based ILs as adjuvants to adjust phase separation temperatures and biomolecules partition.